Immunological profiles of patients with chronic myeloid leukaemia. I. State before the start of treatment - Humlová, Z; Klamová, H; Janatková, I; Sandová, P; Sterzl, I; Sobotková, E; Hamsíková, E; Haskovec, C; Písacka, M; Cetkovský, P; Michalová, K; Faber, E; et al. (Folia biologica, 2006)
In view of the increasing interest in the immunotherapy of CML it seems highly desirable to broaden the present knowledge on the immune reactivity of CML patients. A group of 24 patients and 24 healthy controls were studied for the total of 15 immunological parameters, including the prevalence of antibodies against human herpesviruses and papillomaviruses. To clearly discriminate between changes associated with the disease and those induced by the therapy, all patients were enrolled prior to the start of any anti-leukaemic therapy. Statistically significant differences between patients and controls were found in the levels of IgA, C4 component of complement, CRP and IL-6, the production of Th1 cytokines in stimulated CD3 cells and the E. coli stimulatory index. The analysis of the interrelationship between the results obtained in the individual patients presented some unexpected findings, such as the lack of correlation between the CRP and IL-6 levels. It will be the purpose of a follow-up to determine whether and how the immune status of the patients prior to the treatment correlates with their response to therapy and how the individual immunological profiles change in the course of the disease. These observations will be utilized in the future immunotherapeutic studies to constitute the vaccine- and placebo-treated groups.
Keywords: senioři; C-Reactive Protein; podskupiny lymfocytů; Phagocytosis; Papillomaviridae; interleukin-6; Male; lidský herpesvirus 2; Interleukin-6; C-reaktivní protein; Middle Aged; komplement C3; mužské pohlaví; Herpesvirus 1, Human; Lymphocyte Subsets; studie případů a kontrol; Complement C3; Antibodies, Viral; Adult; Complement C4; Follow-Up Studies; fagocytóza; komplement 4; následné studie; ženské pohlaví; Humans; chronická myeloidní leukemie; lidský herpesvirus 1; autoprotilátky; lidé středního věku; protilátky virové; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; dospělí; Herpesvirus 2, Human; Female; Aged; Autoantibodies; lidé; Case-Control Studies